2019
DOI: 10.1007/s13205-019-1718-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential anticancer applications of the novel naringin-based ruthenium (II) complex

Abstract: Ruthenium seems to be a promising alternative to platinum because of the wide range of oxidation states it has and its ability to form complexes with bioactive ligands. In this study, naringin, a naturally occurring flavonoid, was used to synthesize a novel ruthenium complex with potential anticancer activity. The characterization of the synthesized complex was done by UV-Vis spectroscopy, FTIR and NMR studies. In addition, the complex was tested against Human A549 cell lines to determine the anticancer effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Naringin was used to fabricate a ruthenium complex with anticancer activity. Results showed that a naringin-ruthenium (II) complex reduced cell viability and proliferation, and promoted apoptosis in A549 human lung adenocarcinoma ( Garcia et al, 2019 ). Also, treatment with naringin alone and in combination with transition metal ions [Ag (I), Y (III), and Ru (III)] reduced cell growth and viability, and enhanced apoptosis in A549 human lung adenocarcinoma.…”
Section: Anticancer Activities Of Naringinmentioning
confidence: 99%
“…Naringin was used to fabricate a ruthenium complex with anticancer activity. Results showed that a naringin-ruthenium (II) complex reduced cell viability and proliferation, and promoted apoptosis in A549 human lung adenocarcinoma ( Garcia et al, 2019 ). Also, treatment with naringin alone and in combination with transition metal ions [Ag (I), Y (III), and Ru (III)] reduced cell growth and viability, and enhanced apoptosis in A549 human lung adenocarcinoma.…”
Section: Anticancer Activities Of Naringinmentioning
confidence: 99%
“…Amidst flavonoids, quercetin and its metal complexes have been studied in terms of DNA binding studies, in order to establish structure-activity relationships [58]. Recently, Ru [59][60][61][62][63][64][65][66], V [67,68], Zn [69], Cu [70,71], Fe [72] and La [73] complexes bearing bioactive flavonoids or related ligands have been described. This also include half-sandwich ruthenium [74][75][76][77], rhodium [74,75] and osmium [75,78] derivatives that exhibit cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, naringin regulated the proliferation of HepG2 hepatocellular carcinoma cell line [79] . Further, naringinbased synthetic ruthenium complex showed anticancer potential against A549 human cell line without any toxicity on dermal fibroblasts [80] .…”
Section: Naringin and Cancer Cellsmentioning
confidence: 95%